Development of a sensitive setup for laser spectroscopy studies of very exotic calcium isotopes. (22nd February 2017) - Ruiz, R F Garcia; Gorges, C; Bissell, M; Blaum, K; Gins, W; Heylen, H; Koenig, K; Kaufmann, S; Kowalska, M; Krämer, J; Lievens, P; Malbrunot-Ettenauer, S; et al.
Abstract: An experimental setup for sensitive high-resolution measurements of hyperfine structure spectra of exotic calcium isotopes has been developed and commissioned at the COLLAPS beam line at ISOLDE, CERN. The technique is based on the radioactive detection of decaying isotopes after optical pumping and state selective neutralization (ROC) (Vermeeren et al 1992 Phys. Rev. Lett. 68 1679 ). The improvements and developments necessary to extend the applicability of the experimental technique to calcium isotopes produced at rates as low as few ions s –1 are discussed. Numerical calculations of laser-ion interaction and ion-beam simulations were explored to obtain the optimum performance of the experimental setup. Among the implemented features are a multi-step optical pumping region for sensitive measurements of isotopes with hyperfine splitting, a high-voltage platform for adequate control of low-energy ion beams and simultaneous β -detection of neutralized and remaining ions. The commissioning of the experimental setup, and the first online results on neutron-rich calcium isotopes are presented.